A full solid-state electrochromic device based on gradient ion conductor and co-sputtering anode and a preparation method thereof

CN122883395APending Publication Date: 2026-10-09ZHEJIANG JINGSHENG FILM TECH CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202611271030.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-20
Publication Date
2026-10-09

AI Technical Summary

Technical Problem

[0005](1)界面稳定性与响应速度的矛盾:传统的单一材料离子导体层难以同时与阴极和阳极材料形成最优界面

Benefits of technology

[0050](1)本申请采用的梯度离子导体层,可以分别优化与阴极电致变色层和阳极电致变色层的界面,以降低阻抗、提升响应速度并从根本上增强界面稳定性,延长寿命;梯度离子导体层为阴阳极提供了量身定制的最佳界面,大幅降低了Li+在界面的传输能垒,使着色和褪色响应时间缩短30%以上;梯度离子导体层可以分别与阴极电致变色层和阳极电致变色层形成超稳定的梯度界面,从根本上抑制了长期循环中的界面退化与副反应,使器件寿命有望突破30000次循环,可靠性极大提升。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure FT_1
    Figure FT_1
  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The application relates to a full-solid-state electrochromic device based on a gradient ion conductor and a co-sputtering anode and a preparation method thereof. The full-solid-state electrochromic device comprises, from bottom to top, a transparent substrate layer, a first transparent conductive layer, a cathode electrochromic layer, a gradient ion conductor layer, an anode electrochromic layer and a second transparent conductive layer. The gradient ion conductor layer comprises a first ion conductor layer and a second ion conductor layer. The first ion conductor layer and the second ion conductor layer are different in material and are independently selected from any one of lithium tantalate and lithium niobate. Alternatively, the first ion conductor layer and the second ion conductor layer both comprise lithium tantalum niobium oxide. By adopting the gradient ion conductor layer, the interfaces with the cathode layer and the anode layer are respectively optimized, so that the impedance is reduced, the response speed is improved, the interface stability is fundamentally enhanced, and the service life is prolonged.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This application relates to the field of electrochromic electronic thin film components, and in particular to an all-solid-state electrochromic device based on a gradient ion conductor and a co-sputtered anode and its fabrication method. Background Technology

[0002] The widely adopted electrochromic technology, which reversibly adjusts light transmittance by applying low voltage, is a key technology for achieving intelligent energy-saving dimming. High-performance electrochromic devices generally adopt a complementary all-solid-state structure of "cathode layer / ion conductor layer / anode layer", in which the anode and cathode layers work together to color / fade.

[0003] Existing technologies typically employ a layered structure consisting of a glass substrate / fluorine-doped tin oxide (FTO) electrode / tungsten trioxide (WO3) cathode layer / a single ion-conducting layer (such as tantalum oxide Ta2O5) / nickel oxide (NiO) anode layer / indium tin oxide (ITO) electrode. In this structure, WO3 is reduced to produce a blue color, and NiO is oxidized to produce a brown color; the two are superimposed to achieve an approximate black color. The Ta2O5 layer is responsible for conducting Li. + And isolate electronics.

[0004] However, existing all-solid-state complementary electrochromic devices generally suffer from three interrelated core technical problems:

[0005] (1) The contradiction between interface stability and response speed: Traditional single-material ion conductor layers are difficult to form an optimal interface with both cathode and anode materials at the same time. Poor interfaces lead to high ion transport resistance, slow response speed, and are prone to side reactions during long-term cycling, which significantly shortens the device life.

[0006] (2) Bottleneck of anode material performance: Commonly used anode materials (such as pure nickel oxide) still have a certain intrinsic absorption in the completely faded state, which limits the upper limit of the overall transmittance of the device; at the same time, its coloring efficiency needs to be improved, and the thickness often needs to be increased in order to achieve deep coloring, thus sacrificing response speed and transparency.

[0007] (3) Low overall performance ceiling: Due to the above two points, existing devices are difficult to meet the requirements of high-end applications at the same time in terms of three key indicators: high optical contrast (bright in faded state and deep black in colored state), fast response (second-level switching) and ultra-long cycle life (>20,000 times).

[0008] CN116300233A discloses an electrochromic element with a high switching rate, comprising, in sequence, a first glass substrate (1); a first transparent oxide conductive layer (2); an anode electrochromic layer (3); an electron isolation layer (4); an ion storage layer (5); a cathode electrochromic layer (6); a second transparent oxide conductive layer (7); and a second glass substrate (8); wherein the cathode electrochromic layer is formed by coating a gel onto the ion storage layer.

[0009] CN117192858A discloses a film structure and its fabrication method for a wide-range spectral tunable device. The film structure, from bottom to top, includes a substrate, a bottom electrode layer, an ion storage layer, an electrolyte layer, an electrochromic layer, and a top electrode layer. The substrate material is polyimide, polyester, perfluoroethylene propylene, quartz glass, or cerium-doped glass; the bottom electrode layer is made of ITO; the ion storage layer is made of nickel oxide; the electrolyte layer is made of LiTaO3, LiPO4, or LiNbO3; the electrochromic layer is made of WO3; and the top electrode layer is made of Al, Ag, or ITO. The overall structure is a lattice structure.

[0010] The main drawbacks of the above-mentioned prior art are: (1) "One-size-fits-all" ion conductor layer: The ion conductor layer of a single material (such as Ta2O5) cannot be optimized for the different chemical properties of the anode and cathode materials. This results in high ion transport impedance at the interface, slow response, and instability and easy degradation of the interface during long-term electrochemical cycling; (2) Inherent defects of anode materials: Pure NiO has insufficient transparency in the fading state and generally low coloring efficiency. To achieve deep coloring, its thickness often needs to be increased, which in turn reduces the transmittance and response speed of the fading state, forming a performance paradox; (3) Poor performance balance: Due to the above-mentioned material and interface problems, traditional structural devices cannot achieve a balance between optical contrast, response speed and cycle life, and cannot meet the stringent requirements of high-end smart windows and other applications for comprehensive performance.

[0011] Therefore, there is an urgent need for a new all-solid-state electrochromic device and its fabrication method, so as to obtain an all-solid-state electrochromic device with significantly improved overall performance. Summary of the Invention

[0012] To address the aforementioned technical problems, this application provides an all-solid-state electrochromic device based on a gradient ion conductor and a co-sputtered anode, and its fabrication method. By introducing a gradient ion conductor layer and a co-sputtered tungsten-doped nickel oxide anode with precisely controllable composition, this application enables the all-solid-state electrochromic device to exhibit faster response speed, higher optical contrast and neutral color, longer cycle life, and better process controllability and consistency.

[0013] To achieve this objective, the following technical solution is adopted in this application:

[0014] In a first aspect, this application provides an all-solid-state electrochromic device based on a gradient ion conductor and a co-sputtered anode, wherein the all-solid-state electrochromic device comprises, from bottom to top: a transparent substrate layer, a first transparent conductive layer, a cathode electrochromic layer, a gradient ion conductor layer, an anode electrochromic layer, and a second transparent conductive layer;

[0015] The gradient ion conductor layer includes a first ion conductor layer and a second ion conductor layer; the first ion conductor layer and the second ion conductor layer are made of different materials, and each is independently selected from either lithium tantalate or lithium niobate;

[0016] Alternatively, both the first and second ion conductor layers may be made of lithium tantalum niobium oxide.

[0017] The gradient ion conductor layer used in this application can optimize the interface with the cathode electrochromic layer and the anode electrochromic layer respectively, thereby reducing impedance, improving response speed, and fundamentally enhancing interface stability and extending lifetime. The gradient ion conductor layer provides a customized optimal interface for the anode and cathode, significantly reducing Li + The transport barrier at the interface reduces the coloring and fading response time by more than 30%; the gradient ion conductor layer can form an ultra-stable gradient interface with the cathode electrochromic layer and the anode electrochromic layer respectively, which fundamentally suppresses interface degradation and side reactions in long-term cycling, making the device lifespan expected to exceed 30,000 cycles and greatly improving reliability.

[0018] In some embodiments, the transparent substrate layer is made of soda-lime glass or a flexible polymer.

[0019] In some embodiments, the material of the first transparent conductive layer includes fluorine-doped tin oxide.

[0020] In some embodiments, the material of the second transparent conductive layer includes indium tin oxide; the thickness of the second transparent conductive layer is 300-400nm, such as 300nm, 320nm, 340nm, 360nm, 380nm, 400nm, etc., but is not limited to the listed values, and other unlisted values ​​within the above range are also applicable.

[0021] The thickness of the second transparent conductive layer specified in this application can ensure that the top electrode has low sheet resistance and achieve uniform coloring of large-area devices.

[0022] In some embodiments, the flexible polymer includes any one of polyethylene terephthalate, polyethylene naphthalate, polyimide, polycarbonate, polymethyl methacrylate, polyethersulfone, cyclic olefin polymers, cyclic olefin copolymers, polyurethane, or polydimethylsiloxane.

[0023] In some embodiments, the cathode electrochromic layer is made of tungsten trioxide; the thickness of the cathode electrochromic layer is 300-400 nm, such as 300 nm, 320 nm, 340 nm, 360 nm, 380 nm, 400 nm, etc., but is not limited to the listed values, and other unlisted values ​​within the above range are also applicable.

[0024] In some embodiments, the first ion conductor layer is located above the cathode electrochromic layer; the second ion conductor layer is located above the first ion conductor layer.

[0025] In some embodiments, the first ion conductor layer is made of lithium tantalate.

[0026] The first ionic conductor layer in this application is made of lithium tantalate, which has good energy level matching with WO3 interface, stable chemical properties, and can effectively suppress interfacial side reactions. + Injecting WO3 provides an efficient channel.

[0027] In some embodiments, the thickness of the first ion conductor layer is 20-60 nm, such as 20 nm, 25 nm, 30 nm, 35 nm, 40 nm, 45 nm, 50 nm, 55 nm, 60 nm, etc., but is not limited to the listed values. Other unlisted values ​​within the above range are also applicable.

[0028] In some embodiments, the second ion conductor layer is made of lithium niobate.

[0029] The second ion conductor layer in this application is made of lithium niobate, which has better compatibility with nickel-based anodes and can further reduce the interface impedance on the anode side, promoting Li + Quick embedding / de-embedding.

[0030] In some embodiments, the thickness of the second ion conductor layer is 80-150 nm, such as 80 nm, 85 nm, 90 nm, 95 nm, 100 nm, 110 nm, 120 nm, 130 nm, 140 nm, 150 nm, etc., but is not limited to the listed values. Other unlisted values ​​within the above range are also applicable.

[0031] In some embodiments, the total thickness of the gradient ion conductor layer is 100-210 nm, such as 100 nm, 105 nm, 110 nm, 115 nm, 130 nm, 150 nm, 170 nm, 190 nm, 200 nm, 205 nm, 210 nm, etc., but is not limited to the listed values. Other unlisted values ​​within the above range are also applicable.

[0032] The total thickness of the gradient ion conductor layer, as defined in this application, is crucial for balancing the performance of all-solid-state electrochromic devices. Too thin a layer (e.g., <70 nm) can lead to microscopic defects causing electron leakage (e.g., short circuits); too thick a layer (e.g., >300 nm) increases ion migration resistance, resulting in higher operating voltage and slower response. This application achieves lower ion transport impedance while ensuring absolute electronic insulation by optimizing the total thickness of the gradient ion conductor layer.

[0033] The gradient ion conductor layer design of this application abandons the "one-size-fits-all" approach of using a single material and achieves "divide and conquer" of the interface. While ensuring extremely high electronic insulation, it greatly optimizes ion transport dynamics and long-term interface stability.

[0034] In some embodiments, the thickness of the anodic electrochromic layer is 200-280 nm, such as 200 nm, 210 nm, 220 nm, 230 nm, 240 nm, 250 nm, 260 nm, 270 nm, 280 nm, etc., but is not limited to the listed values. Other unlisted values ​​within the above range are also applicable.

[0035] The thickness of the anodic electrochromic layer specified in this application can both fully complement the cathode layer to achieve a deep color state (transmittance can be less than 10%) and maintain a high transmittance in the faded state.

[0036] In some embodiments, the anodic electrochromic layer is made of metal-doped nickel oxide.

[0037] The anodic electrochromic layer of this application is made of metal-doped nickel oxide. The anodic electrochromic layer with high coloring efficiency complements the WO3 cathode electrochromic layer more effectively, achieving a deeper coloring state that is closer to neutral black (transmittance can be less than 10%). At the same time, its high fading state transparency ensures the overall high optical modulation amplitude (ΔT).

[0038] In some embodiments, the doped metal includes any one or a combination of at least two of tungsten, molybdenum, or tantalum, with typical but non-limiting examples of such combinations being tungsten-molybdenum, tungsten-tantalum, or molybdenum-tantalum.

[0039] In some embodiments, the ratio of the total number of atoms of the doped metal to the number of atoms of nickel is 5:95 to 15:85, such as 5:95, 6:94, 7:93, 8:92, 9:91, 10:90, 11:89, 13:87, 15:85, etc., but is not limited to the listed values. Other unlisted values ​​within the above range are also applicable.

[0040] This application achieves high optical contrast by optimizing the thickness of the anodic electrochromic layer and the tungsten doping ratio. This specific doping ratio effectively improves the optical and electrochemical properties of nickel oxide, thereby significantly increasing its transparency in the tarnished state. Simultaneously, the material at this ratio exhibits high coloring efficiency, ensuring that at the specified thickness, it can achieve a deep coloration state by fully complementing the cathode layer, without excessively sacrificing the transmittance of the tarnished state due to excessive thickness. This parameter combination is the result of experimentally verified optimization in this application.

[0041] Secondly, this application provides a method for fabricating an all-solid-state electrochromic device as described in the first aspect. The method includes: in the same vacuum chamber, under the condition of maintaining a vacuum environment, using a continuous magnetron sputtering process, sequentially depositing a first transparent conductive layer, a cathode electrochromic layer, a gradient ion conductor layer, an anode electrochromic layer, and a second transparent conductive layer on a transparent substrate to obtain the all-solid-state electrochromic device.

[0042] The continuous magnetron sputtering process described in this application is performed without disrupting the vacuum environment, enabling atomically clean interfaces. This avoids the significant increase in ion transport resistance and the emergence of performance degradation caused by minute contamination at the interface. The full sputtering process employed in this application, particularly the co-sputtering preparation of the anode layer, achieves precise control over composition and thickness, ensuring consistent and repeatable device performance and facilitating large-scale production.

[0043] It should be noted that this application does not impose specific requirements or special limitations on the specific sputtering parameters (such as power, gas pressure, atmosphere ratio, substrate temperature, etc.) of the continuous magnetron sputtering process. Those skilled in the art can determine the specific sputtering parameters through conventional experiments.

[0044] In some embodiments, the anodic electrochromic layer is prepared by co-reactive sputtering of a nickel metal target and a doped metal target;

[0045] The doped metal target includes any one or a combination of at least two of the following: tungsten target, molybdenum target, or tantalum target.

[0046] The anodic electrochromic layer of this application is prepared by co-reactive sputtering of a nickel metal target and a doped metal target. By independently adjusting the sputtering power of the two targets, the doping ratio of metal elements can be precisely, continuously, and repeatedly controlled.

[0047] In some embodiments, the preparation method further includes: encapsulating and electrochemically pre-lithiating the obtained all-solid-state electrochromic device.

[0048] It should be noted that after all film layers are deposited, the all-solid-state electrochromic device described in this application does not yet contain a sufficient amount of freely mobile lithium ions in its internal gradient ion conductor layer and electrochromic layer. Therefore, a one-time "electrochemical pre-lithiation" process is necessary to provide it with the ion source required for normal operation. This process typically involves connecting the pre-packaged device to an external lithium metal source in an inert atmosphere glove box, applying a brief DC voltage to drive lithium ions to be injected from the external lithium source and stored inside the device. This step is a common and necessary post-processing step in the fabrication of such all-solid-state lithium-ion electrochromic devices.

[0049] Compared with the prior art, this application has at least the following beneficial effects:

[0050] (1) The gradient ion conductor layer used in this application can optimize the interface with the cathode electrochromic layer and the anode electrochromic layer respectively, so as to reduce impedance, improve response speed and fundamentally enhance interface stability and extend lifetime; the gradient ion conductor layer provides the anode and cathode with a tailor-made optimal interface, which greatly reduces Li + The transport barrier at the interface reduces the coloring and fading response time by more than 30%; the gradient ion conductor layer can form an ultra-stable gradient interface with the cathode electrochromic layer and the anode electrochromic layer respectively, which fundamentally suppresses interface degradation and side reactions in long-term cycling, making the device lifespan expected to exceed 30,000 cycles and greatly improving reliability.

[0051] (2) The material of the anodic electrochromic layer of this application includes metal-doped nickel oxide. The anodic electrochromic layer with high coloring efficiency complements the WO3 cathode electrochromic layer more effectively, achieving a deeper coloring state that is closer to neutral black (transmittance can be less than 10%). At the same time, its high fading state transparency ensures the overall high optical modulation amplitude (ΔT).

[0052] (3) This application achieves high optical contrast by optimizing the thickness of the anodic electrochromic layer and the doping ratio of tungsten. This specific doping ratio effectively improves the optical and electrochemical properties of nickel oxide, thereby significantly increasing its transparency in the fading state. At the same time, the material at this ratio has high coloring efficiency, so that at the specified thickness, it can fully complement the cathode layer to achieve a deep coloring state without excessively sacrificing the transmittance of the fading state due to excessive thickness. This parameter combination is the optimized result verified by experiments in this application.

[0053] (4) The continuous magnetron sputtering process of this application is carried out without destroying the vacuum environment, which can achieve an atomically clean interface, thereby avoiding the fact that micro-contamination at the interface will greatly increase the ion transport resistance and become the source of performance degradation. The full sputtering process used in this application, especially the co-sputtering preparation of the anode layer, achieves precise control of composition and thickness, ensuring the consistency and repeatability of device performance, which is conducive to large-scale production.

[0054] (5) The all-solid-state electrochromic device of this application has the following characteristics: driving voltage ≤ ±3V; visible light transmittance (550nm) in the faded state ≥ 68%; visible light transmittance in the colored state ≤ 10%; response time (90% change) < 20 seconds; and cycle life (ΔT decay < 20%) > 20,000 times. Attached Figure Description

[0055] Figure 1 This is a schematic diagram of the structure of an all-solid-state electrochromic device based on a gradient ion conductor and a co-sputtered anode provided in this application.

[0056] Among them, 101 is a transparent substrate layer; 102 is a first transparent conductive layer; 103 is a cathode electrochromic layer; 104 is a gradient ion conductor layer; 104a is a first ion conductor layer; 104b is a second ion conductor layer; 105 is an anode electrochromic layer; and 106 is a second transparent conductive layer. Detailed Implementation

[0057] The technical solution of this application will be further described below with reference to the accompanying drawings and specific embodiments. However, the examples below are merely simplified examples of this application and do not represent or limit the scope of protection of this application. The scope of protection of this application shall be determined by the claims.

[0058] Example 1

[0059] This embodiment provides an all-solid-state electrochromic device based on a gradient ion conductor and a co-sputtered anode, the structural schematic of which is shown below. Figure 1 As shown. The all-solid-state electrochromic device comprises, from bottom to top: a transparent substrate layer 101, a first transparent conductive layer 102, a cathode electrochromic layer 103, a gradient ion conductor layer 104, an anode electrochromic layer 105, and a second transparent conductive layer 106;

[0060] The gradient ion conductor layer 104 includes a first ion conductor layer 104a and a second ion conductor layer 104b.

[0061] The transparent substrate 101 is made of soda-lime glass;

[0062] The first transparent conductive layer 102 is made of fluorine-doped tin oxide;

[0063] The second transparent conductive layer 106 is made of indium tin oxide and has a thickness of 350 nm;

[0064] The cathode electrochromic layer 103 is made of tungsten trioxide and has a thickness of 350 nm.

[0065] The first ion conductor layer 104a is located above the cathode electrochromic layer 103; the second ion conductor layer 104b is located above the first ion conductor layer 104a.

[0066] The first ion conductor layer 104a is made of lithium tantalate and has a thickness of 40 nm.

[0067] The second ion conductor layer 104b is made of lithium niobate and has a thickness of 120 nm.

[0068] The total thickness of the gradient ion conductor layer 104 is 160 nm;

[0069] The thickness of the anodic electrochromic layer 105 is 240 nm; the material of the anodic electrochromic layer 105 is tungsten-doped nickel oxide; the ratio of the number of tungsten atoms to the number of nickel atoms is 10:90.

[0070] This embodiment also provides a method for fabricating the all-solid-state electrochromic device, the method comprising: in the same vacuum chamber, under the condition of maintaining a vacuum environment, using a continuous magnetron sputtering process, sequentially depositing a first transparent conductive layer 102, a cathode electrochromic layer 103, a gradient ion conductor layer 104, an anode electrochromic layer 105, and a second transparent conductive layer 106 on a transparent substrate layer 101 to obtain the all-solid-state electrochromic device; and encapsulating and electrochemically pre-lithiating the obtained all-solid-state electrochromic device;

[0071] The anodic electrochromic layer 105 is prepared by co-reactive sputtering of a nickel metal target and a tungsten metal target;

[0072] The working principle of the all-solid-state electrochromic device described in this embodiment is as follows: when a coloring voltage is applied between the upper and lower transparent conductive layers (102 and 106) (for example, 102 is connected to negative and 106 is connected to positive):

[0073] Li + and e - Inject WO3 layer (103) to restore its color (blue);

[0074] Li + and e - From WNiO x Extracted from layer (105) and oxidized to a dark brown color;

[0075] Li +Charge flows through the external circuit via the migration between the two layers through the gradient ion conductor layer (104);

[0076] The blue of WO3 and WNiO x The dark brown overlays give the device an overall neutral black appearance, significantly reducing its transmittance.

[0077] When a reverse voltage is applied, the process is completely reversed, ions migrate in the opposite direction, and the device returns to a highly transparent state.

[0078] Example 2

[0079] This embodiment provides an all-solid-state electrochromic device based on a gradient ion conductor and a co-sputtered anode, the structural schematic of which is shown below. Figure 1 As shown. The all-solid-state electrochromic device comprises, from bottom to top: a transparent substrate layer 101, a first transparent conductive layer 102, a cathode electrochromic layer 103, a gradient ion conductor layer 104, an anode electrochromic layer 105, and a second transparent conductive layer 106;

[0080] The gradient ion conductor layer 104 includes a first ion conductor layer 104a and a second ion conductor layer 104b.

[0081] The transparent substrate 101 is made of polyethylene terephthalate;

[0082] The first transparent conductive layer 102 is made of fluorine-doped tin oxide;

[0083] The second transparent conductive layer 106 is made of indium tin oxide and has a thickness of 300 nm;

[0084] The cathode electrochromic layer 103 is made of tungsten trioxide and has a thickness of 300 nm.

[0085] The first ion conductor layer 104a is located above the cathode electrochromic layer 103; the second ion conductor layer 104b is located above the first ion conductor layer 104a.

[0086] The first ion conductor layer 104a is made of lithium niobate and has a thickness of 20 nm.

[0087] The second ion conductor layer 104b is made of lithium tantalate and has a thickness of 80 nm.

[0088] The total thickness of the gradient ion conductor layer 104 is 100 nm;

[0089] The thickness of the anodic electrochromic layer 105 is 200 nm; the material of the anodic electrochromic layer 105 is tungsten-molybdenum-doped nickel oxide; the ratio of the total number of tungsten-molybdenum atoms to the number of nickel atoms is 5:95;

[0090] This embodiment also provides a method for fabricating the all-solid-state electrochromic device, the method comprising: sequentially depositing a first transparent conductive layer 102, a cathode electrochromic layer 103, a gradient ion conductor layer 104, an anode electrochromic layer 105, and a second transparent conductive layer 106 on a transparent substrate layer 101 using a continuous magnetron sputtering process to obtain the all-solid-state electrochromic device; and encapsulating and electrochemically pre-lithiating the obtained all-solid-state electrochromic device.

[0091] The anodic electrochromic layer 105 is prepared by co-reactive sputtering of a nickel metal target and a tungsten-molybdenum alloy target.

[0092] Example 3

[0093] This embodiment provides an all-solid-state electrochromic device based on a gradient ion conductor and a co-sputtered anode, the structural schematic of which is shown below. Figure 1 As shown. The all-solid-state electrochromic device comprises, from bottom to top: a transparent substrate layer 101, a first transparent conductive layer 102, a cathode electrochromic layer 103, a gradient ion conductor layer 104, an anode electrochromic layer 105, and a second transparent conductive layer 106;

[0094] The gradient ion conductor layer 104 includes a first ion conductor layer 104a and a second ion conductor layer 104b.

[0095] The transparent substrate 101 is made of polyimide;

[0096] The first transparent conductive layer 102 is made of fluorine-doped tin oxide;

[0097] The second transparent conductive layer 106 is made of indium tin oxide and has a thickness of 400 nm;

[0098] The cathode electrochromic layer 103 is made of tungsten trioxide and has a thickness of 400 nm.

[0099] The first ion conductor layer 104a is located above the cathode electrochromic layer 103; the second ion conductor layer 104b is located above the first ion conductor layer 104a.

[0100] The first ion conductor layer 104a is made of lithium tantalum niobium oxide and has a thickness of 60 nm.

[0101] The second ion conductor layer 104b is made of lithium tantalum niobium oxide and has a thickness of 150 nm.

[0102] The total thickness of the gradient ion conductor layer 104 is 210 nm;

[0103] The thickness of the anodic electrochromic layer 105 is 280 nm; the material of the anodic electrochromic layer 105 is tungsten-tantalum doped nickel oxide; the ratio of the total number of tungsten-tantalum atoms to the number of nickel atoms is 15:85.

[0104] This embodiment also provides a method for fabricating the all-solid-state electrochromic device, the method comprising: sequentially depositing a first transparent conductive layer 102, a cathode electrochromic layer 103, a gradient ion conductor layer 104, an anode electrochromic layer 105, and a second transparent conductive layer 106 on a transparent substrate layer 101 using a continuous magnetron sputtering process to obtain the all-solid-state electrochromic device; and encapsulating and electrochemically pre-lithiating the obtained all-solid-state electrochromic device.

[0105] The anodic electrochromic layer 105 is prepared by co-reactive sputtering of a nickel metal target and a tungsten-tantalum alloy target.

[0106] Example 4

[0107] This embodiment provides an all-solid-state electrochromic device based on a gradient ion conductor and a co-sputtered anode. The difference from Embodiment 1 is that the total thickness of the gradient ion conductor layer 104 is adjusted to 70 nm, while all other aspects are the same as in Embodiment 1.

[0108] Example 5

[0109] This embodiment provides an all-solid-state electrochromic device based on a gradient ion conductor and a co-sputtered anode. The difference from Embodiment 1 is that the total thickness of the gradient ion conductor layer 104 is adjusted to 300 nm, while all other aspects are the same as in Embodiment 1.

[0110] Example 6

[0111] This embodiment provides an all-solid-state electrochromic device based on a gradient ion conductor and a co-sputtered anode. The difference from Embodiment 1 is that the thickness of the anode electrochromic layer 105 is adjusted to 180 nm, while all other aspects are the same as in Embodiment 1.

[0112] Example 7

[0113] This embodiment provides an all-solid-state electrochromic device based on a gradient ion conductor and a co-sputtered anode. The difference from Embodiment 1 is that the thickness of the anode electrochromic layer 105 is adjusted to 300 nm, while all other aspects are the same as in Embodiment 1.

[0114] Example 8

[0115] This embodiment provides an all-solid-state electrochromic device based on a gradient ion conductor and a co-sputtered anode. The difference from Embodiment 1 is that the anode electrochromic layer 105 is made of tungsten-doped nickel oxide; the ratio of the number of tungsten atoms to the number of nickel atoms is 3:97, and all other aspects are the same as in Embodiment 1.

[0116] Example 9

[0117] This embodiment provides an all-solid-state electrochromic device based on a gradient ion conductor and a co-sputtered anode. The difference from Embodiment 1 is that the anode electrochromic layer 105 is made of tungsten-doped nickel oxide; the ratio of the number of tungsten atoms to the number of nickel atoms is 17:83, and all other aspects are the same as in Embodiment 1.

[0118] Comparative Example 1

[0119] This comparative example provides an all-solid-state electrochromic device based on a gradient ion conductor and a co-sputtered anode. The difference from Example 1 is that the gradient ion conductor layer 104 is replaced with lithium tantalate of equal material and thickness, while all other aspects are the same as in Example 1.

[0120] Comparative Example 2

[0121] This comparative example provides an all-solid-state electrochromic device based on a gradient ion conductor and a co-sputtered anode. The difference from Example 1 is that the gradient ion conductor layer 104 is replaced with lithium niobate of equal thickness, while all other aspects are the same as in Example 1.

[0122] Comparative Example 3

[0123] This comparative example provides an all-solid-state electrochromic device based on a gradient ion conductor and a co-sputtered anode. The difference from Example 1 is that the material and thickness of the anode electrochromic layer 105 are replaced with nickel oxide, while all other aspects are the same as in Example 1.

[0124] Performance testing

[0125] The driving voltage, visible light transmittance in the faded state, visible light transmittance in the colored state, response time, and cycle life (ΔT decay < 20%) of the all-solid-state electrochromic devices prepared in Examples 1-9 and Comparative Examples 1-3 were tested, and the results are shown in Table 1.

[0126] Table 1

[0127]

[0128] The test results show that:

[0129] (1) As can be seen from Examples 1 to 3, the all-solid-state electrochromic device of this application significantly improves the performance of the all-solid-state electrochromic device by adopting a gradient ion conductor layer and a metal-doped anode electrochromic layer. Ultimately, its driving voltage is ≤ ±3V; the visible light transmittance in the faded state (550nm) is ≥68%; the visible light transmittance in the colored state is ≤10%; the response time (90% change) is <20 seconds; and the cycle life (ΔT decay <20%) is >20,000 times.

[0130] (2) By comparing Example 1 with Examples 4-9, it can be seen that by optimizing the thickness of the gradient ion conductor layer, the thickness of the anodic electrochromic layer and the metal doping ratio of the anodic electrochromic layer, this application can further improve the response time, cycle stability, colored state transmittance and faded state transmittance of the all-solid-state electrochromic device.

[0131] (3) By comparing Example 1 with Comparative Examples 1-3, it can be seen that in Comparative Examples 1 and 2, replacing the gradient ion conductor layer with a single lithium tantalate and lithium niobate respectively resulted in a significant decrease in the response time and cycle stability of the all-solid-state electrochromic device; in Comparative Example 2, replacing the tungsten-doped nickel oxide anode electrochromic layer with a nickel oxide layer resulted in a significant decrease in the colored state transmittance and the faded state transmittance of the all-solid-state electrochromic device.

[0132] In summary, this application provides an all-solid-state electrochromic device based on a gradient ion conductor and a co-sputtered anode, and its fabrication method. The gradient ion conductor layer can optimize the interface with both the cathode and anode electrochromic layers, thereby reducing impedance, improving response speed, and fundamentally enhancing interface stability and extending lifetime. The gradient ion conductor layer provides a customized optimal interface for the anode and cathode, significantly reducing Li-induced impedance. + The transport barrier at the interface reduces the coloring and fading response time by more than 30%; the gradient ion conductor layer can form an ultra-stable gradient interface with the cathode electrochromic layer and the anode electrochromic layer respectively, which fundamentally suppresses interface degradation and side reactions in long-term cycling, making the device lifespan expected to exceed 30,000 cycles and greatly improving reliability.

[0133] The applicant declares that the above description is only a specific implementation of this application, but the protection scope of this application is not limited thereto. Those skilled in the art should understand that any changes or substitutions that can be easily conceived by those skilled in the art within the scope of the technology disclosed in this application fall within the protection and disclosure scope of this application.

Claims

1. A fully solid-state electrochromic device based on a gradient ion conductor and a co-sputtered anode, characterized in that, The all-solid-state electrochromic device comprises, from bottom to top: a transparent substrate layer, a first transparent conductive layer, a cathode electrochromic layer, a gradient ion conductor layer, an anode electrochromic layer, and a second transparent conductive layer; The gradient ion conductor layer includes a first ion conductor layer and a second ion conductor layer; the first ion conductor layer and the second ion conductor layer are made of different materials, and each is independently selected from either lithium tantalate or lithium niobate; Alternatively, both the first and second ion conductor layers may be made of lithium tantalum niobium oxide.

2. The all-solid-state electrochromic device according to claim 1, characterized in that, The transparent substrate layer is made of materials including soda-lime glass or flexible polymer; And / or, the material of the first transparent conductive layer includes fluorine-doped tin oxide; And / or, the material of the second transparent conductive layer includes indium tin oxide; the thickness of the second transparent conductive layer is 300-400 nm.

3. The all-solid-state electrochromic device according to claim 2, characterized in that, The flexible polymer includes any one of polyethylene terephthalate, polyethylene naphthalate, polyimide, polycarbonate, polymethyl methacrylate, polyethersulfone, cyclic olefin polymer, cyclic olefin copolymer, polyurethane, or polydimethylsiloxane; And / or, the material of the cathode electrochromic layer includes tungsten trioxide; the thickness of the cathode electrochromic layer is 300-400 nm.

4. The all-solid-state electrochromic device according to claim 1, characterized in that, The first ion conductor layer is located above the cathode electrochromic layer; the second ion conductor layer is located above the first ion conductor layer; And / or, the first ion conductor layer is made of lithium tantalate and has a thickness of 20-60 nm; And / or, the second ion conductor layer is made of lithium niobate and has a thickness of 80-150 nm.

5. The all-solid-state electrochromic device according to claim 1, characterized in that, The total thickness of the gradient ion conductor layer is 100-210 nm; And / or, the thickness of the anodic electrochromic layer is 200-280 nm.

6. The all-solid-state electrochromic device according to claim 1, characterized in that, The anodic electrochromic layer is made of metal-doped nickel oxide.

7. The all-solid-state electrochromic device according to claim 6, characterized in that, The doped metal includes any one or a combination of at least two of tungsten, molybdenum, or tantalum; And / or, the ratio of the total number of atoms of the doped metal to the number of atoms of nickel is 5:95 to 15:

85.

8. A method for fabricating an all-solid-state electrochromic device as described in any one of claims 1-7, characterized in that, The preparation method includes: in the same vacuum chamber, under the condition of maintaining a vacuum environment, using a continuous magnetron sputtering process, sequentially depositing a first transparent conductive layer, a cathode electrochromic layer, a gradient ion conductor layer, an anode electrochromic layer and a second transparent conductive layer on a transparent substrate to obtain the all-solid-state electrochromic device.

9. The preparation method according to claim 8, characterized in that, The anodic electrochromic layer was prepared by co-reactive sputtering of a nickel metal target and a doped metal target. The doped metal target includes any one or a combination of at least two of the following: tungsten target, molybdenum target, or tantalum target.

10. The preparation method according to claim 8 or 9, characterized in that, The preparation method further includes: encapsulating and electrochemically pre-lithiating the obtained all-solid-state electrochromic device.

Citation Information

Patent Citations

  • Electrochromic element with high conversion rate and preparation method thereof

    CN116300233A

  • Film system structure of wide-range spectrum adjustable device and preparation method thereof

    CN117192858A